Top Management’s Attention to Discontinuous Technological Change: Corporate Venture Capital as an Alert Mechanism - Maula, Markku V. J.; Keil, Thomas; Zahra, Shaker A. (Organization Science, 2013)
Technological discontinuities pose serious challenges to top managers’ attention. These discontinuities, which often occur at the fringes of an industry, are usually driven by innovative and (often) venture capital-backed start-ups creating new products and transforming existing industries in ways that are difficult for incumbent managers to understand against the backdrop of their existing cognitive schemata. However, failing to appreciate and embrace successful technological discontinuities might endanger incumbents’ very existence. Extending the attention-based view, we explore whether and how interorganizational relationships guide top managers’ attention either to or away from technological discontinuities. We propose that homophilous relationships (e.g., alliances with industry peers) should exhibit a negative relationship with incumbents’ timely attention to technological discontinuities, whereas heterophilous relationships (e.g., with venture capitalists as a result of coinvestments) should exhibit a positive relationship. Furthermore, we hypothesize that the status of the partners strengthens the effect of homophilous and heterophilous relationships with the timely attention of top managers to technological discontinuities. Based on a longitudinal study of the incumbents in four information and communications technology industry sectors, we find that heterophilous ties through corporate venture capital (CVC), coinvesting with high-status venture capital firms, exhibit a strong positive relationship with timely attention. CVC, when it connects senior management to high-status venture capitalists through coinvestments, has a special role in directing top managers’ attention to technological discontinuities and ensuing business opportunities. Implications for the understanding of the role of interorganizational ties as structural determinants of top managers’ attention are discussed.